Media Bantu Analisis Superposisi Gelombang dengan Amplitudo dan Fasa Awal Berbeda Menggunakan MATLAB - Nurullaeli, Nurullaeli; Nugraha, Alpi Mahisha (UNIVERSITAS INDRAPRASTA PGRI, 2024)
Manual calculations for the superposition of more than 2 waves that have different amplitudes and initial phases are quite complicated so that assistive media is needed that can be used to analyze this phenomenon. The purpose of this research is to create a assistive media to analyze the superposition of waves with different amplitudes and initial phases. Analysis of the wave superposition formula using trigonometry formula and phasor method. Meanwhile, the calculation algorithm is written in the MATLAB programming language which is packaged in a GUI (Graphical User Interface) using the GUIDE facility. This media can be used to calculate wave equations and wave quantities resulting from the superposition of 2 or more waves. This media is also equipped with wave simulations resulting from superposition in the time domain. This media can be one of the innovative learning media to increase students understanding of wave material and at the same time provide examples of the application of the GUI in MATLAB.